2006
DOI: 10.1038/sj.bjp.0706911
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by α‐Tetrahydrodeoxycorticosterone (THDOC) of Pre‐Sympathetic Parvocellular Neurones in the Paraventricular Nucleus of Rat Hypothalamus

Abstract: Background and Purpose: a-tetrahydrodeoxycorticosterone (THDOC) is an endogenous neuroactive steroid which increases in plasma and brain concentration during stress. It has both positive and negative modulatory effects on GABA activated GABA A currents, dependent upon the dose. We investigated the effects of THDOC on spinally-projecting ''pre-sympathetic'' neurones in the parvocellular subnucleus of the hypothalamic paraventricular nucleus (PVN), to determine whether it activates or inhibits these neurones, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Past studies showed that THDOC positively modulates GABA A receptor currents in parvocellular neurons of the paraventricular nucleus of the hypothalamus (Womack et al 2006). Fluctuation in neurosteroid concentration is associated with altered neural expression of GABA A receptor subtypes (Concas et al 1998) and GABA release (for a review, see Helms et al 2012c).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies showed that THDOC positively modulates GABA A receptor currents in parvocellular neurons of the paraventricular nucleus of the hypothalamus (Womack et al 2006). Fluctuation in neurosteroid concentration is associated with altered neural expression of GABA A receptor subtypes (Concas et al 1998) and GABA release (for a review, see Helms et al 2012c).…”
Section: Discussionmentioning
confidence: 99%
“…5␣-Reductase and 3␣-HSD also metabolize 11-deoxycorticosterone (DOC), from the adrenal cortex, to 3␣,5␣-tetrahydrodeoxycorticosterone (TH-DOC), a neurosteroid acting like allopregnanolone (Womack et al, 2006). DOC secretion is increased by acute stress (Reddy and Rogawski, 2002a), but finasteride actions via decreased TH-DOC formation in the current study are unlikely because corticosterone levels in pregnant rats were no greater than in virgins.…”
Section: Allopregnanolone-synthesizing Enzymesmentioning
confidence: 93%
“…In common, the output of spinally projecting parvocellular neurons is similarly reduced by low concentrations of 5α3α-THDOC (Womack et al, 2006). Neuroendocrine parvocellular neurons are known to activate the HPA axis through the release of CRH (Vale et al, 1981) and i.c.v.…”
Section: Physiological and Pathophysiological Role Of Neurosteroids: mentioning
confidence: 99%